Vicissitudes in access to drinking water in municipalities of the Metropolitan Region of Salvador/BA - Neves, Virginia Silva; Baiardi, Amilcar (Seven Editora, 2023)
The difficulties related to access to water are real and aggravate the quality of life on the planet. In Brazil it is no different and full access to water for public supply and also for other uses can be considered a challenge for administrators at all levels of power. This article aims to highlight the insufficiency of basic sanitation and access to drinking water in the Metropolitan Region of Salvador (RMS) and how far these services are from the goals of the United Nations. Preliminarily, a picture of basic sanitation at the national level is drawn, its historical process of institutionalization and the past and present difficulties for offering quality of this service. The text also considers that technological choices and the state of the art have part of the responsibility for the lack of water supply service. The investigation takes place in the area of applied social sciences, with a qualitative-quantitative approach and a descending hypothetical-deductive conduct, situated in the more general conceptual and epistemological field of the evaluation of municipal public policies, focusing on the evaluation of public sanitation policy. It is expected as a result that it can be useful for the management and for sanitation policies at the municipal level. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-145